PENGARUH PROFITABILITAS, LIKUIDITAS, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG (Studi pada Perusahaan Otomotif & Komponen yang terdaftar di Bursa Efek Indonesia periode 2014 – 2018) - Masyaili (FEB Universitas Lakidende, 2020)
This study aims to determine the effect of profitability, liquidity, sales growth, firm size and institutional ownership on debt policy on automotif and component company in BEI 2014-2018 period. This study used a methods multiple regression data analysis. The results showed that in partial profitability and liquidity variables have no influence on debt policy while variable sales growth, firm size and institutional ownership have influence on debt policy on automotif and component company. Simultaneously, the variable profitability, liquidity, sales growth, firm size and institutional ownership have influence on debt policy on automotif and component company